Long noncoding RNA plasmacytoma variant translocation 1 is overexpressed in cutaneous squamous cell carcinoma and exon 2 is critical for its oncogenicity - Li Chen; Sun Chengxi; Mahapatra Kunal Das; Riihilä Pilvi; Knuutila Jaakko; Nissinen Liisa; Lapins Jan; Kähäri Veli-Matti; Homey Bernhard; Sonkoly Enikö; Pivarcsi Andor (Oxford University Press, 2025)
Background: Cutaneous squamous cell carcinoma (cSCC) is one of the most common and fastest increasing forms of cancer worldwide with metastatic potential. Long non-coding RNAs (lncRNAs) are a group of RNA-molecules with essential regulatory functions for both physiological and pathological processes.
Objectives: To investigate the function and mode of action of lncRNA plasmacytoma variant translocation 1 (PVT1) in cSCC.
Methods: The expression level of PVT1 was quantified in normal skin, premalignant skin lesion actinic keratosis (AK) and cSCCs by qRT-PCR and single molecule in situ hybridization. The function of PVT1 in cSCC was investigated both in vivo (tumour xenograft) and in vitro (competitive cell growth assay, EdU-incorporation assay, colony formation assay and tumour spheroid formation assay) by CRISPR-Cas9-mediated knockout of the entire PVT1 locus or PVT1 exon 2, and by locked nucleic acid (LNA) GapmeR-mediated PVT1-knockdown. RNA-seq-analysis was conducted to identify genes and processes regulated by PVT1.
Results: We identified PVT1 as a lncRNA upregulated in cutaneous squamous cell carcinoma in situ (cSCCIS) and cSCC and associated with oncogenic phenotype of cSCC. The increased expression of PVT1 in cSCC was regulated by MYC. Both CRISPR-Cas9-deletion of the entire PVT1 locus and LNA GapmeR-mediated knockdown of PVT1-transcript impaired the malignant behaviour of cSCC cells which suggested that PVT1 is an oncogenic transcript in cSCC. Furthermore, knockout of PVT1 exon 2 inhibited cSCC tumour growth both in vivo and in vitro demonstrating that exon 2 is a critical element for the oncogenic role of PVT1. Mechanistically, we showed that PVT1 was localized in the cell nucleus and acted as a suppressor of cellular senescence by inhibiting CDKN1A expression and preventing cell cycle arrest.
Conclusions: Our study reveals a previously unrecognized role for exon 2 of PVT1 in its oncogenic role and that PVT1 suppresses cellular senescence in cSCC. PVT1 may be a biomarker and therapeutic target in cSCC.